Karakteristik kimia biscuit dari tepung porang (Amorphophallus muelleri) dan jagung (Zea mays) sebagai emergency food product: Formulasi dan pretreatment adonan - Gusti Ananda Syahputri; Rahma Bayunita Hapsari; Kania Uswama (Politeknik Negeri Lampung., 2024)
Emergency Food Product (EFP) is a special food used in emergencies such as disasters by paying attention to criteria such as safe, palatable, easy to distribute, easy to consume, and nutritionally complete. Biscuits are processed products that can be developed to meet EFP criteria. Biscuits have a crunchy and dry texture so that they can last a long time and are favored by the majority of people. The main ingredient in making biscuits is wheat flour. However, it can be modified by utilizing local commodities such as porang and corn. Therefore, research needs to be done to get the right formulation for making biscuits made from local flour so that they can meet EFP criteria. This study used the factorial Complete Randomized Design (RAL) method, which consists of two factors, local flour formulation and dough pretreatment temperature. Analysis of the chemical characteristics including moisture, ash, protein, fat, carbohydrate, crude fiber content, and calories. The results showed that the formulation provided significant differences in moisture, ash, fat, protein, crude fiber, and carbohydrate content of local flour biscuit prototypes. The temperature difference of pretreatment (-18°C or 4°C) for 30 minutes before molding provides significant differences in moisture, fat, crude fiber, and carbohydrate content of local flour biscuit prototypes. Based on the number of calories per 50 gr of products, all prototypes of local flour biscuits with pretreatment at -18°C showed calories with an average of 234 kcal, meeting the calorie density requirements of emergency food products, which is a minimum of 233 kcal / 50 gr and a maximum of 250 kcal / 50 gr